Acute Stroke due to Electrocution: Uncommon or Unrecognized? - Laxmi Kokatnur; Mohan Rudrappa (Case Reports in Neurological Medicine)
The growing dependence on electricity in our daily lives has increased the incidence of electrocution injuries. Although several neurological injuries have been described previously, acute stroke due to electrocution is rare. Our patient, a previously healthy man, was electrocuted after he grabbed a “live” high-voltage wire. Although he was hemodynamically stable, he remained confused with language defects. MRI of the brain showed acute stroke in the bilateral anterior cerebral artery territory and watershed regions of the left middle cerebral artery territory. MR angiogram incidentally showed A1 segment aplasia of the right anterior cerebral artery. Electrocution is known to cause vasospasm leading to end-organ damage similar to that seen in stroke. In our patient, vasospasm of the left anterior circulation likely led to watershed infarcts in the left parietal lobe and bilateral frontal lobes. Due to aplasia of the A1 segment on the right side, perfusion to both frontal lobes was solely from the left anterior cerebral artery.